2014
DOI: 10.1111/1753-6405.12206
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood nutrition concerns, resources and services for Aboriginal families in Victoria

Abstract: Objective: To investigate the child nutrition concerns of Aboriginal families with young children attending Aboriginal health and early childhood services in Victoria; training needs of early childhood practitioners; and sources of nutrition and child health information and advice for Aboriginal families with young children. Method:Qualitative needs assessment involving consultation with Aboriginal parents of young children aged 0-8 years attending Aboriginal health and early childhood services, and early chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 38 publications
(39 reference statements)
1
33
0
Order By: Relevance
“…This finding might indicate the benefits of further building capacity in child nutrition among AHW (as well as other health providers). Previous research has identified a need to build nutrition expertise among AHW (5,29) , including providing AHW clear and contextually relevant information to disseminate to families (29,67) and building AHW confidence in delivering correct nutritional messages (5) . Training gaps have also been identified for other health providers working in Aboriginal and Torres Strait Islander infant and child health (5,6,63) .…”
Section: Health Provider Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding might indicate the benefits of further building capacity in child nutrition among AHW (as well as other health providers). Previous research has identified a need to build nutrition expertise among AHW (5,29) , including providing AHW clear and contextually relevant information to disseminate to families (29,67) and building AHW confidence in delivering correct nutritional messages (5) . Training gaps have also been identified for other health providers working in Aboriginal and Torres Strait Islander infant and child health (5,6,63) .…”
Section: Health Provider Interactionsmentioning
confidence: 99%
“…Colonisation disconnected Aboriginal and Torres Strait Islander people from their family, land, culture and traditional knowledge, and has contributed to ongoing trauma (30,31) . Colonial practices such as relocating Aboriginal and Torres Strait Islander people to missions, the provision of food rations and separating mothers from their children interrupted intergenerational knowledge transfer, contributing to the loss of knowledge about infant feeding practices (5)(6)(7)29,32,33) . Further, the colonisation of Australia led to persisting social, economic, health and structural inequities for Aboriginal and Torres Strait Islander peoples (30,34) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…also established research partnerships, strengthening the evidence base for practice with four university collaborations resulting in research publications. 17,[20][21][22][23] Supervised dietetic student placements further built dietitian-Aboriginal community linkages, for example, the implementation of the Aboriginal Community Food Programs Success Stories project. 24 Community feedback further informed the roll-out of food programs within the SecondBite partnership.…”
Section: Partnership Developmentmentioning
confidence: 99%
“…workshops) and in MEND child overweight and obesity training sessions with Aboriginal health professionals and community workers. They strengthened the practice evidence base through community consultation, systematic evaluation, ongoing cycles of action-reflection and community dissemination as well as the disciplinary evidence base through research, publication 5,17,[20][21][22][23][24][31][32][33][34][35][36][37] and presentations. Importantly, they also embedded the VANPAS across the emergent system of the Victorian Aboriginal nutrition sector.…”
Section: Leadership Developmentmentioning
confidence: 99%